TUNNEL LIGHTING FOR VEHICLES IN DKI JAKARTA - Setyaningsih, Endah; Pragantha, Jeanny; Wardhani, Lydwina (FSTPT Indonesia, 2015)
Tunnel, a subsidiary structure of the street, must have lighting system in accordance with the public street lighting. Many streets in DKI Jakarta don’t have sufficient lighting, and so do tunnels. This research aim is to know the lighting of two tunnels, located on Tomang junction and Jl. TB Simatupang, by measuring illuminance and luminance with light meter. Night time illuminance of first tunnel is 32 - 120 lux. Illuminance of second tunnel is 53 - 163 lux. Theses values are far above SNI value which is 20 - 25 lux. Meanwhile the lighting before tunnel entrance and after exit zone are not sufficient (below 8 lux), causing driver’ sight to feel uncomfortable when he enters or exits tunnel (black hole effect). HPS lamps of Tomang tunnel give yellow color impression but TB Simatupang tunnel gives white-yellow color impression because of alternate installation of HPS lamps with some LED lamps on treshold zone. These conditions show that there isn’t good planning in choosing tunnel lamp.